Globalisation and the Genesis of Values - Austin-Broos, Diane (The Australian journal of anthropology, 2003)
This talk was delivered as an Inaugural Lecture in Anthropology at the University of Sydney on the evening of August 22, 2001. It was sponsored by the Arts Association of the University of Sydney. In it I present an overview of my career, noting the consistencies between my work in philosophy and in anthropology, and between what may appear as two quite disparate field sites, urban Jamaica and central Australia. A method that involves a sociology of value, and an historical anthropology, brings these research areas into interesting relations, as does a growing concern with women's roles in the course of change.